“A Meat Locker in Hebron”: Meat Eating, Occupation, and Cruelty in To the End of the Land - Kreuter, Aaron (Pivot: A Journal of Interdisciplinary Studies and Thought, 2019)
In this paper, I explore the connections between meat-eating, cruelty, and the Israeli/Palestinian crisis in Israeli author David Grossman’s 2008 novel To the End of the Land (translated from the Hebrew in 2010 by Jessica Cohen). Using the radical vegetarian-feminist theories of Carol J. Adams, I argue that in the novel, Grossman reveals how the Israeli nation-state’s treatment of the occupied Palestinian people is part and parcel of the same ideological construct that allows its citizens to consume the flesh of dead animals; if a nation can eat meat, it can dehumanize and oppress its unwanted others. In particular, I look at a pivotal moment in the novel, where the protagonist Ora’s son’s military unit leaves an elderly Palestinian man chained up and suffering in a Hebron meat locker; I locate this event as the most important physical space in a novel preoccupied with space, land, and physicality. I also look at another example of a Jewish author grappling with the cruelty of eating meat, the Yiddish writer Isaac Bashevis Singer’s short story "The Slaughterer." Finally, I interrogate the idea, put forward by Todd Hasak-Lowy, that Grossman is less concerned with the sufferings of the Palestinian people than he is the sufferings of the stoic Israeli, forced to make compromising moral choices.